Aging and Weight-Ratio Perception - Holmin, Jessica S. (Public Library of Science, 2012)
Past research has provided evidence that older adults have more difficulty than younger adults in discriminating small differences in lifted weight (i.e., the difference threshold for older adults is higher than that of younger adults). Given this result, one might expect that older adults would demonstrate similar impairments in weight ratio perception (a suprathreshold judgment) compared to younger adults. The current experiment compared the abilities of younger and older adults to perceive weight ratios. On any given trial, participants lifted two objects in succession and were asked to provide an estimate of the objects’ weight ratio (the weight of the heavier object relative to the lighter). The results showed that while the older participants’ weight ratio estimates were as reliable as those of the younger participants, they were significantly less accurate: the older participants frequently perceived the weight ratios to be much higher than they actually were.